(untitled) (Journal of Health, Population and Nutrition, 2010)
This study evaluated the magnitude and distribution of acute gastrointestinal illness (GI) in Gálvez, Argentina, and assessed the outcome of a seven-day versus 30-day recall period in survey methodology. A crosssectional population survey, with either a seven-day or a 30-day retrospective recall period, was conducted through door-to-door visits to randomly-selected residents during the ’high’ and the ’low’ seasons of GI in the community. Comparisons were made between the annual incidence rates obtained using the sevenday and the 30-day recall period. Using the 30-day recall period, the mean annual incidence rates was 0.43 (low season of GI) and 0.49 (high season of GI) episodes per person-year. Using the seven-day recall period, the mean annual incidence rate was 0.76 (low season of GI) and 2.66 (high season of GI) episodes per person-year. This study highlights the significant burden of GI in a South American community and confirms the importance of seasonality when investigating GI in the population. The findings suggest that a longer recall period may underestimate the burden of GI in retrospective population surveys of GI. Key words: Cross-sectional studies; Developing country; Diarrhoea; Foodborne diseases; Morbidity; Population surveys; Recall bias; Waterborne diseases; Argentina DOI: 10.3329/jhpn.v28i2.4885 J Health Popul Nutr 2010 Apr; 28(2): 149-158